Dialogue with Europe, dialogue with the past: colonial Nahua and Quechua elites in their own words - Olko, Justyna, editor; Sullivan, John, editor; Szemi?ski, Jan, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
A critical anthology of indigenous-authored texts, including Nahua, Quechua, and Spanish which native peoples and Spaniards convey their perspectives on Spanish colonial order. The first volume with native testimonies of Spanish expansion and examines geographically and culturally realities of indigenous elites in the colonial period.--Provided by publisher.
Keywords: Mexico -- History -- Spanish colony, 1540-1810 -- Sources; Peru -- History -- Conquest, 1522-1548 -- Sources; Nahuas -- Mexico -- History -- Sources; Quechua Indians -- Peru -- History -- Sources; Nahuatl language -- Texts; Quechua language -- Texts; Spanish language -- Texts; Elite (Social sciences) -- Mexico -- History; Elite (Social sciences) -- Peru -- History